PERBANDINGAN INTERPRETASI HASIL UJI TUBEX TF DAN ELISA PADA PEMERIKSAAN IgM ANTI SALMONELLA TYPHI - Herlinawati, Herlinawati (Nusantara Hasana Journal, 2022)
Typhoid fever is an acute systemic infectious disease caused by Salmonella typhi. According to the world health organization (WHO) 2003, is predicted there are about 17 million cases of typhoid fever in the entire world with incidence 600,000 cases of deaths every year. In Indonesia, is predicted there are about 900.000 cases with incidence >20.000 cases of deaths every year. The diagnosis of typhoid fever is done clinically and by laboratory examination especially by serodiagnostic test. Various serodiagnostic test that used to detect IgM anti Salmonella typhi are TUBEX TF and ELISA. The present study was aimed to understand the comparison interpretation TUBEX TF test and ELISA in detect IgM anti Salmonella typhi. This study was observational analysis with cross sectional study design. Sampling technique used was consecutive sampling. The total sample were 44 samples all examined with the TUBEX TF and ELISA. Research results showed that 24 samples (54.5%) were positive and 20 samples (45.5%) were negative with TUBEX TF examination, while 6 samples (13.6 %) were positive and 38 samples (86.4%) were negative with ELISA examination. Statistical analysis from Mc Nemar test showed that the two instruments differ significantly (p=0.000) and from Kappa conformity test showed that the conformity of two instruments was low (0.233). Statistical analysis from Spearman correlation test showed that TUBEX TF and ELISA had middleand significant positive correlation (r=0.446; p=0.002). There was still different interpretation between TUBEX TF test and ELISA in detect IgM anti Salmonella typhi.